A new species of Trichocenthrus from Ecuador (Heteroptera: Colobathristidae), with a key to the species of the genus - Coscarón, María Del Carmen; Dellapé, Pablo Matías (Zootaxa, 2003)
Trichocentrus ecuatorianus n. sp. (Heteroptera: Colobathristidae) is described and illustrated from Ecuador. The value of the male genitalia for separating species is discussed. A key to all known species of Trichocenthrus is included.